Cyber Security for Cyber Physical Systems - Ali, Saqib; Al Balushi, Taiseera; Nadir, Zia; Hussain, Omar Khadeer (Studies in Computational Intelligence,, 2018)
This book is a pioneering yet primary general reference resource on cyber physical systems and their security concerns. Providing a fundamental theoretical background, and a clear and comprehensive overview of security issues in the domain of cyber physical systems, it is useful for students in the fields of information technology, computer science, or computer engineering where this topic is a substantial emerging area of study. .